PENGARUH INFLASI, NILAI TUKAR RUPIAH, SUKU BUNGA, DAN PROFITABILITAS TERHADAP RETURN SAHAM PERUSAHAAN CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BEI TAHUN 2013 – 2017 - Suci Mardina; Suprihatmi Sri Wardiningsih; Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this research was to analyze the significance of the effect of Inflation, Rupiah Exchange Rates (Kurs), Interest Rates (BI Rate), and ROA on the Stock Returns Of Consumer Goods Industry Companies listed on Indonesia Stock Exchange in the period of 2013 - 2017. The population in this research ware all Consumer Goods Industry Companies listed on the Indonesia Stock Exchange in the period 2013 -2017 wich amounted to 49 companies, the number of sample use in this research were 23 companies, with the sampling technique using purposive sampling method. The data analysis technique use in this research is a Classical Assumption Test, Analysis of Multiple Linear Regression, t-Test, F-test, dan Determination Coefficient. The reuslts obtained in this research inicate that partially Inflation dan Interest Rate (BI Rate) variabels have a negative and not significant effect on Stock Returns, and the Exchange Rate of Rupiah (Kurs) and ROA variabels have a positive and significant effect on Stock Returns. Simultaneously Inflation, Rupiah Exchange Rate, Interest Rate (BI Rate), and ROA have a Significant Effect influance Stock Returns.